2023
DOI: 10.26668/businessreview/2023.v8i10.3520
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training on Improving Employee Performance: A Case Study on Employees in the Directorate of Education of Ma'an District

Essam Deep Al Khawaldeh

Abstract: Purpose: The aim of this study is to determine the impact of training on improving the performance of workers in Maan's Directorate of Education.   Theoretical framework: This study will focus on finding a cognitive dimension that contributes to clarifying the concept of training and its dimensions (type of training, training period, trainers) and its impact on the job performance of employees.   Design/Methodology/Approach: The descriptive analytical approach was used in the study. The study sample included 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The strategy's relevance is further increased by involving input from all organizational levels and external stakeholders, educating all stakeholders, and making outcomes publicly available. Implementing open strategies successfully depends on ongoing training, cultural changes, and an appreciation of the importance of group knowledge [49].…”
Section: Effectiveness Of Open Strategymentioning
confidence: 99%
“…The strategy's relevance is further increased by involving input from all organizational levels and external stakeholders, educating all stakeholders, and making outcomes publicly available. Implementing open strategies successfully depends on ongoing training, cultural changes, and an appreciation of the importance of group knowledge [49].…”
Section: Effectiveness Of Open Strategymentioning
confidence: 99%
“…New opportunities for personal development can be explored by doing additional research that covers extensive topics, benchmarking, case studies, reports, market requirements, and diverse practitioner articles. (Khawaldeh, 2023) studied the impact of training on improving the performance of workers in Maan's Directorate of Education. This researcher found that there is a moderate effect of overall training on the improvement of worker's performance due to the trainer's dimension, but the other dimensions of quality training and its duration do not impact worker's performance.…”
Section: )mentioning
confidence: 99%
“…Regarding training resources, the authors recommend improving their availability and management. The concept of employee education in terms of type, duration, and lectors is explored in Khawaldeh [6] in the context of a case study.…”
mentioning
confidence: 99%